Ethnic-based separation in maternity Departments in Israel - a balanced practical view - Jonathan Halevy (BMC, 2018)
Abstract Ethnic-based separation in public hospitals in Israel is a sensitive issue that was recently brought forward by the media and was recently discussed in the Israel Journal of Health Policy Research. The above paper maintains that ethnic separation in inpatient rooms does take place some of the time and this runs contrary to the ethos of neutrality in medicine. The authors recommend implementing a national policy that prohibits ethnic-based separation in hospital inpatient rooms. In this commentary I point to the fact that the authors' research indicates that often times ethnic separation is not based on racism, and while the call for unequivocal prohibition of discriminatory ethnic-based separation is of course morally justified, such an across-the-board prohibition is actually an imposition of mixed rooms under all circumstances. I recommend a more balanced and still ethically acceptable approach: any request by patients for a separate room that is overtly based on ethnic discrimination should be immediately rejected and that hospital directors should be called upon by the Ministry of Health not to take a back seat on this issue, to be proactive in explaining to the staff the importance of absolute avoidance of any discriminatory considerations in the placement of patients, and to monitor the extent of ethnic separation expecting to see in every department ethnically mixed rooms.